PERSEPSI WISATAWAN TERHADAP DESTINASI PARIWISATA HALAL DI ACEH UTARA - Ayu Safitri; Fadliyatul Masja; Agustinawati (Seminar Nasional Bidang Kesehatan, Ekonomi, Pendidikan dan Kemasyarakatan (SINAS TAMPAN), 2022)
Halal tourism destinations are a leading regional tourism sector. This research was conducted to determine tourists’ perceptions of halal tourism in North Aceh. This study uses a descriptive qualitative approach. Data was obtained through distributing questionnaires to tourists in tourism destinations. The data analysis method used is multiple regression. The research results show that the facility variable has a very significant effect on tourists’ perceptions of the Lancok beach tourism destination in North Aceh